241 Remotely Delivered Yoga Nidra for Insomnia and Anxiety during COVID-19. (3rd May 2021) - Sharpe, Erica; Butler, Matthew; Hanes, Doug; Bradley, Ryan
Abstract: Introduction: Insomnia and related anxiety affect 30 - 50% of the US adult population. These conditions often coexist, and contribute to increased mortality from depression, heart disease, and stroke. The current COVID-19 pandemic has heightened anxiety and sleeplessness, and 53% of US adults report the pandemic has affected their mental health. There is a need for research into therapies for anxiety and insomnia that can be delivered remotely for increased accessibility to reach more individuals in need. Methods: To contribute to this need, we examined the effects of remotely delivered Yoga Nidra (translated to mean "yogic sleep"), a guided meditation practice, on anxiety and sleep. The practice was delivered in real-time before bed, or asynchronously via an online REDCap-based platform, once per week for 16-weeks from April to July (during the early months of the COVID-19 pandemic). Results: Seventy-four individuals joined the study, of whom 71% reported subthreshold insomnia (Insomnia Severity Index score of 14 ± 4), and 74% reported anxiety (Generalized Anxiety Disorder Index score of 10 ± 5). Seventy-one (96%) participants accessed the asynchronous recordings. Remote delivery of this practice proved very feasible, with no adverse events reported, and although we provided no monetary compensation, 50% of our sample still completed a post-intervention survey. Further, 52% of n=25 respondents who completed both pre- and post-intervention sleep surveys reported decreased sleep onset latency (SOL) the following day, with a mean decrease of 10 minutes (95% CI = −19.0, −0.5) for all respondents, and strongest change (−34 min; p=.017) measured for those who reported SOL between 30-120 min at baseline. Overall state anxiety was decreased by 41% for n=32 respondents who completed pre-post State Trait Anxiety Index (STAI) surveys surrounding a single practice (average score of 47 ± 11 before practice vs. 27 ± 8 after practice, p<.0001). Conclusion: Remotely delivered Yoga Nidra is feasible to deliver, and demonstrates potential benefits for anxiety and insomnia, warranting additional research. Support (if any): This work was supported by the R90 BRIDG grant at the Helfgott Research Institute at the National University of Natural Medicine.